Religious Radicalism, Global Terrorism and Islamic Challenges in Contemporary Indonesia - Choirul Mahfud; Niken Prasetyawati; Wahyuddin; Zainul Muhibbin; Dyah Satya Yoga Agustin; Heni Sukmawati (Institut Teknologi Sepuluh Nopember, 2018)
Discussing the radicalism of religion and global terrorism is a globalchallenge that is now a worldwide concern, including for the Islamiccommunity in Indonesia. Research in this paper with an analytical descriptiveapproach using the documentative method. The general purpose of thisresearch is to understand the root causes of terrorism and religiousradicalism in Indonesia? What is the solution of Islam to overcome theproblem of religious radicalism and global terrorism? The results of thisresearch show: first, the historical roots of global terrorism and religiousradicalism is a very complex portrait of social, political, and economichistory. Also, the complexity of local, regional and global problems areinterconnected with one another. Second, the Islamic solution to overcomethis problem with the Islamic approach to peace for all (rahmatan lil alamin)which prioritizes the path of dialogue and world peace.